Low‐Temperature Oxidation‐Processed Titanium Oxides as Dual‐Functional Electron‐Selective Passivation Contacts. Issue 4 (10th December 2019) - Wang, Wei; Yang, Zhenhai; Wang, Zhixue; Lin, Hao; Wang, Jiajia; Liao, Mingdun; Zeng, Yuheng; Yan, Baojie; Ye, Jichun
Abstract : Passivation contact (PSC), which simultaneously achieves high passivation quality and low contact resistivity, has been proven to be a delicate design to fabricate high‐efficiency solar cells (SCs). However, traditional PSC materials, that is, intrinsic a‐Si:H/doped a‐Si:H or tunnel SiO2 /doped poly‐Si, overly rely on the complex procedures and have inevitable optical or Auger recombination losses. Herein, a novel low‐temperature oxidation (LTO) process is developed and an electron‐selective TiO x film (LTO‐TiO x ) is fabricated, reaching a low‐effective surface recombination velocity of 13.7 cm s −1 . The high‐quality passivation performance is mainly attributed to the chemical passivation of Ti–O–Si bonds and the surface carrier manipulation ability of the LTO‐TiO x film. Next, by adding a low work function (WF) layer of LiF x film, the surface band bending effect is formed and the contact resistivity of TiO x ‐based PSC is also optimized. Furthermore, the dual‐functional LTO‐TiO x /LiF x electron‐selective PSC is integrated in Si SCs and a champion efficiency is achieved near 19% with an open‐circuit voltage near 640 mV. Finally, a comprehensive simulation analysis indicates a high efficiency of more than 22% based on LTO‐TiO x PSC, followed by a detailed roadmap of efficiency improvements, demonstrating its huge application potential in SCs. Abstract : A novel low‐temperature oxidation process is developed to fabricate titanium oxide films. Combined with the insertion of a low work function layer of LiF film, a dual‐functional passivation contact simultaneously suppressing the minority carrier recombination and assisting majority carrier transport is achieved, of which the performance has been successfully verified in the device level.